2019
DOI: 10.1080/21691401.2019.1593999
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA (hsa_circ_0051240) promotes cell proliferation, migration and invasion in ovarian cancer through miR-637/KLK4 axis

Abstract: View related articles View Crossmark data Citing articles: 13 View citing articles Circular RNA (hsa_circ_0051240) promotes cell proliferation, migration and invasion in ovarian cancer through miR-637/KLK4 axis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 27 publications
2
58
0
Order By: Relevance
“…For instance, circPLEKHM3 was down-regulated in OC and identified as a tumor inhibitor by the miR-9/BRCA1/DNAJB6/KLF4/ AKT1 axis; 9 Guan et al illuminated that circPUM1 was up-regulated and improved the tumorigenesis of OC via targeting miR-615-5p or miR-6753-5p. 10 We noticed the up-regulation of circ_0025033 in OC tissues in a recent study, 11 while the report about its biological function in OC has not been published.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, circPLEKHM3 was down-regulated in OC and identified as a tumor inhibitor by the miR-9/BRCA1/DNAJB6/KLF4/ AKT1 axis; 9 Guan et al illuminated that circPUM1 was up-regulated and improved the tumorigenesis of OC via targeting miR-615-5p or miR-6753-5p. 10 We noticed the up-regulation of circ_0025033 in OC tissues in a recent study, 11 while the report about its biological function in OC has not been published.…”
Section: Introductionmentioning
confidence: 99%
“…Studies also found that circRNAs regulated the malignant biological behavior of ovarian cancer cells [16]. For example, circEXOC6B and circN4BP2L2 may act as novel prognostic biomarkers in patients with epithelial ovarian cancer [17], circ_0051240 promotes cell proliferation, migration and invasion in ovarian cancer [18], and circ-HIPK3 is an important regulator of ovarian cancer progression [19]. Besides, our study found that circRNA-UBAP2 was highly expressed in ovarian cancer tissues and cell lines.…”
Section: Discussionmentioning
confidence: 53%
“…MiR-196a-5p also interacts directly with the 3'UTR of ZMYND11 and promotes the growth of GBM cells (35). Finally, miR-637 has been reported to be a tumor suppressor gene in diverse human cancers, such as gastric (36), ovarian (37) and colorectal cancers (38). Results in human glioma are consistent with a function as a tumor suppressor; expression levels of miR-637 were significantly reduced in clinical glioma tissues compared with normal brain tissues (39).…”
Section: Discussionmentioning
confidence: 71%